Construction management of power transmission lines - logistics and challenges - Mohd. Yusof, Zulkifli; Sivadass, T. (2006)
Power transmission line is an interconnection from generating stations, may it be thermal or hydro, to load centers catering for industrial, commercial and domestic consumers of electricity. It comprises of a combination of components in a multi-discipline blend of electrical, structural and geotechnical engineering. The construction of power transmission lines has always been a challenge to the power industry utilities as it involves positioning and installation of tall towers on rugged terrains, inaccessibility of land transportations in remote areas, minimizing damages to crops and paddy fields, scarcity of rentice in urban developed areas, right-of-way (wayleave) management, sensitivities of land-use, constraints pertaining to the electricity supply regulation requirements, aesthetics and environmental considerations. Managing transmission line construction logistics is a specialized craft by itself. Heavy masses of structural steelwork, construction materials for concrete foundations, reels of conductor cables, transmission line fittings and accessories, and heavy stringing machineries such as tensioners and pullers need to be transported to hilltops or swampy areas. This paper provides an informative overview of the current construction practices and the management of logistics for the installation of power transmission lines in this region, the challenges facing the utilities and regulators for a sustainable construction, and the sharing of knowledge, technical information and experience on a specialized field of engineering construction.